Correction: Ameliorations in dyslipidemia and atherosclerotic plaque by the inhibition of HMG-CoA reductase and antioxidant potential of phytoconstituents of an aqueous seed extract of Acacia senegal (L.) Willd in rabbits. - Jaykaran Charan; Priyanka Riyad; Heera Ram; Ashok Purohit; Sneha Ambwani; Priya Kashyap; Garima Singh; Abeer Hashem; Elsayed Fathi Abd Allah; Vijai Kumar Gupta; Ashok Kumar; Anil Panwar (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0264646.].